Casas e seus entornos: o reassentamento com bônus moradia na cidade de Porto Alegre/RS - Ahlert, Betina (2012)
This paper s theme is popular housing and the government actions on Housing Policy. The object of analysis is the resettlement with housing bonus in the Integrated Socioenvironmental Program of Porto Alegre s City Government. The target of this study is to analyze how the resettlement with housing bonus occurs within the mentioned program and its relation to the City Government Housing Policy. As a final result, it aims to provide a basis for the resettlement proposals in the Social Concern Housing Policy. As an orientation, this study uses dialectical-critial method, and categories totality, historicity, contradiction, and mediation. We used field research and documentary analysis. During field research, we used data collection, structured interviews with open questions with ten families already resettled, and focal group meeting with eight community leaders participating in the Residents Commission of the Program.The documentary analysis was performed using raw data from forms applied to thirty families by social-technical staff of the Program in 2011. Based on the stakeholders speeches we were able to perceive the complexity of working in the housing field, since it contains objective and subjective family life aspects. Also based on the stakeholders speeches we investigated topics related to the public participation in the resettlement process, aspects related to the living environment, and the two empirically identified categories family and work. We believe that housing bonus is an interesting resettlement alternative when it is performed along with resettlement in housing units. This fact gives the families autonomy in choosing a home. The study points out the need for further research concerning resettlement actions monitoring and post-evaluation, and the need for provide the families with further information in order to reach a conscious and critical process of resettlement.